Procedural Model of Education Quality Management in the Sphere of Physical Culture and Sport of Poland - Mozolev, Oleksandr (Pedagogical Discourse, 2016)
The article reasonably grounds the procedural model of education quality management in the sphere of physical culture and sport of Poland, based on the appropriate selection of the principles, methods and means, which in its complex and interaction formed a mechanism of education quality management and consists of the following procedure blocks: analysis of processes of development of education; forecasting and planning of the development; quality monitoring; the development of innovations; determining the mechanism of implementation of the proposed improvements; examining the compliance of professional competencies of specialists with new requirements. It is clear that each procedure block includes the subprocesses of the education development management quality in the sphere of physical culture and sport, which in general view reflect the content of a function of quality management, namely: development of quality management strategies, implementation of this strategy, monitoring processes and assessment of its effectiveness. It is established that the process of education quality management in the sphere of physical culture and sport is based on normative-legal regulation, which is defined by the legal basis of activity of educational and physical culture and sports organizations. The system of standards of education determines the quality of provided educational services. Normative and legal acts of development of education in the sphere of physical culture and sport regulate managerial influence on the system of education quality and the processes of improvement of quality. It is defined that the system of the quality of education in the sphere of physical culture and sport includes subjects of the educational process which are divided into the establishments of general secondary education, higher education institutions, the system of education of physical culture and sports of different population groups. The effectiveness of the management of the quality of the development of education in the sphere of physical culture and sport largely depends on the organizational structure of management system, its optimum and balance, efficiency and flexibility, timely response to arising problems and on making management decisions. Key words: procedural model, quality control, education, physical training, quality standards.